Stability Analysis of Three-Species Almost Periodic Competition Models with Grazing Rates and Diffusions - Chang-you Wang; Rui-fang Wang; Ming Yi; Rui Li (Discrete Dynamics in Nature and Society)
Almost periodic solution of a three-species competition system with grazing rates and diffusions is investigated. By using the method of upper and lower solutions and Schauder fixed point theorem as well as Lyapunov stability theory, we give sufficient conditions to ensure the existence and globally asymptotically stable for the strictly positive space homogenous almost periodic solution, which extend and include corresponding results obtained by Q. C. Lin (1999), F. D. Chen and X. X. Chen (2003), and Y. Q. Liu, S. L, Xie, and Z. D. Xie (1996).